Ichthyoplankton in the Pánuco river estuary, Tamaulipas-Veracruz - Sánchez-Ramírez, Marina; Ocaña-Luna, Alberto; Berrios-Zamudio, Ariana Lizbet (Ecosistemas y Recursos Agropecuarios, 2021)
To determine the structure of the ichthyoplankton assemblagealong a saline gradient in the Pánuco river estuary, sampling wasperformed in: January, March, May, July, September, and November in 2017at nine sites, with a standard network with a mesh opening of 500 μm. 1165 eggs and 526 fish larvae were collected from 18 species, three of themfrom freshwater. The highest specific richness was observed in the middleestuary and lagoon of Pueblo Viejo. The highest values of diversity andevenness was found in November (2.7 and 0.9, respectively). The dominancewas greatest in July (0.4) due to the abundance of Anchoa mitchilli.The ichthyoplankton assemblage was characterized by a greater number ofdominant marine and estuarine species, a low number of freshwater speciesand a decrease in species richness upstream.